Determinants of fertility desire among married or cohabiting individuals in Rakai, Uganda: a cross-sectional study - Matovu, Joseph K.B.; Makumbi, Fredrick; Wanyenze, Rhoda K.; Serwadda, David (Reproductive health, 2017)
Recent trends in fertility rates indicate declines in total fertility rate (TFR) in some sub-Saharan African countries. However, countries such as Uganda continue to have a persistently high TFR partly attributed to strong preferences for large family sizes. We explored the factors that influence fertility desire among married or cohabiting individuals in Rakai, a rural district in southwestern Uganda. Methods: This cross-sectional study of fertility desire (desire to have another child) was nested in a clusterrandomized demand-creation intervention trial for the promotion of couples’ HIV counseling and testing uptake among married or cohabiting individuals that was conducted in Rakai district between March 1 and April 30, 2015. A total of 1490 married or cohabiting individuals, resident in three study regions with differing background HIV prevalence, were enrolled into the study. Data were collected on socio-demographic, behavioral and fertilityrelated characteristics. We used a modified Poisson regression model to generate prevalence ratio (PR) as a measure of association for factors that were independently associated with fertility desire. We adjusted for clustering at community level and used STATA version 14.0 for all analyses. Results: Overall, fertility desire was high (63.1%, n = 940); higher in men (69.9%, n = 489) than women (57.1%, n = 451). More than three-quarters (78.8%, n = 1174) had 3+ biological children while slightly more than twothirds (68.5%, n = 1020) reported an ideal family size of 5+ children. Only 30% (n = 452) reported that they had attained their desired family size. After adjusting for potential and suspected confounders, the factors that were negatively associated with fertility desire were: age 30–39 (adjusted prevalence ratio [aPR] = 0.82, 95% CI: 0.78, 0.86) and 40+ years (aPR = 0.65, 95% CI: 0.60, 0.71); having six or more biological children (aPR = 0.88, 95% CI: 0.80, 0.97); being HIV-positive (aPR = 0.86, 95% CI: 0.78, 0.95) and ever use of any family planning methods (aPR = 0.93, 95% CI: 0.87, 0.99). Being male (aPR = 1.19, 95% CI: 1.07, 1.33); having primary education (aPR = 1.21, 95% CI: 1.01, 1.44) and having not yet attained the desired family size (aPR = 4.34, 95% CI: 3.50, 5.38) were positively associated with fertility desire
Keywords: Fertility desire; Determinants; Married individuals; Rakai; Uganda